Colloidal and Supported TiO2: Toward Nonextractable and Recyclable Photocatalysts for Radical Polymerizations in Aqueous Dispersed Media. Issue 20 (20th July 2016) - Lobry, Emeline; BT Bah, Abdoul Salam; Vidal, Loïc; Oliveros, Esther; Braun, André M.; Criqui, Adrien; Chemtob, Abraham
Abstract : Two high surface area titania forms, dispersed as stable nanoparticles or coated on fused silica microfiber, are used as nonleachable photocatalysts for the radical photopolymerization of methyl methacrylate miniemulsion in water. At low loading (0.17 wt%/wtmonomer ), both nanoscale TiO2 yield ≈50% conversion after 10 min UV irradiation, compared to 63% with a conventional type I photoinitiatior (hydroxyacetophenone). High‐molecular‐weight values (>180 kDa) and a polydispersity index of about 1.5 are achieved, indicating that undesirable degradation is negligible. In the proposed mechanism, a surface initiation takes place through the generation of hydroxyl radicals from H2 O oxidation. It is shown that irradiance and TiO2 content are two key parameters for controlling molecular weight and conversion values. The supported TiO2 form can be easily recovered and reused up to four times, despite a gradual reduction in conversion. Deposited on the wall of the annular photochemical reactor, it enables reaction scaling‐up. Abstract : Intensively investigated as photocatalysts for the photodegradation of persistent organic contaminants, TiO2 nanomaterials can be tamed to enable miniemulsion photopolymerization. In particular, colloidal and supported titania offer many advantages compared to conventional molecular photoinitiator: facile addition to the monomer dispersion, high surface‐to‐volume ratio, nonmigrating, no byproducts, simple and low cost process, and possible recovery/reuse.